مشاكل التحاسب الضريبي في ظل التجارة الإلكترونية - حسين، وسام نعمة (جامعة تكريت - كلية الإدارة والاقتصاد, 2017)
Recently the E-commerce has been used widely as results of the real revolution in information and communication technology, this revolution parallelized with theoretical conceptualization through the academic, practical, legal, economic, administrative and accounting researches to develop the suitable mechanisms and rules of governing this type of transaction, the role of accounting through several levels has been developing to provide useful accounting information as well as providing essential information for determining the taxable income and settling the tax sales. E commerce taxation needs conceptual framework and general accepting roles to determine the objectivity and fairness taxing operations that what researcher have tried to discuss in this study.
انتشرت وبشكل متزايد في السنوات الأخيرة عمليات التجارة الإلكترونية كأحدى نتائج الثورة الحقيقية في تكنولوجيا المعلومات والاتصالات وتزامنت معها الدراسات والأبحاث الأكاديمية والمهنية القانونية والاقتصادية والإدارية والمحاسبية لوضع أليات وقواعد تحكم هذا النوع من التعاملات، وبرز دور المحاسبة من خلال عدة مستويات في وضع اطر تمكن من توفير معلومات محاسبية بخصائص تتلاءم معها فضلا عن تقديم معلومات أساسية لتحديد الدخل الخاضع للضريبة والتحاسب عن ضريبة المبيعات، إلا أن هذا الدور لا يمكن أن يفي بمتطلبات التحاسب الضريبي ما لم يكن له اطار مفاهيمي يحكم وبصورة عامة وضمن مبادئ وقواعد متفق عليها عمليات التحاسب الضريبي لمعاملات التجارة الإلكترونية بهدف تدعيم موضوعية وعدالة هذا التحاسب وهذا ما حاولت تحديده ووضعه هذه الدراسة.
Keywords: التجارة الإلكترونية -- المحاسبة الضريبية -- المنظمات الافتراضية